Effects Pre-strain of Carbon Steel on Stress-Strain Diagram in CO2 Environment with the Presence of H2S - Asmara, Y. P.; Juliawati, Alias; J., Jaafar; K., Azuar; J. P., Siregar; Kurniawan, Tedi (Academic Research Online Publisher, 2014)
In oil and gas industrial environments, carbon dioxide (CO2) and hydrogen sulfide (H2S) contained in aqueous system are the most common corrosive factors which deteriorate infrastructure made of carbon steel. One of the key factors to accelerate corrosion rate is strain conditions of the steel. Higher strain is suspected to contribute on more hydrogen penetration. This research tested simultaneously the effects pre-strain of carbon steel under saturated CO2 and CO2/H2S environment. The steels were tested in between 5 to 35 percents of initial pre-strain. It showed that the existence of H2S decrease the ultimate tensile strength of the steel. While, the initial pre-strains condition increases the maximum tensile stress. In addition, CO2 and H2S contribute on decreasing toughness.